Risk Assessment Study on Mechanical Connecting Aisle Construction in the Bohai Mudstone Stratum with High Water Pressure - Wencui Zhang; Jian Zhang; Jiaru Luo; Yuanying Lin; Yaohong Zhu (Geofluids)
With the in-depth advancement of underground transportation in China, the connecting aisle is used as a link between different underground spaces to provide sufficient security and connection. The basic structural units of underground and aboveground spaces play an extremely important role. The use of the mechanical connecting aisle construction of over mucky strata is difficult, and it is easy to have an impact on the main tunnel. To ensure the safety of connecting aisle construction, studies should be performed on the construction technology, equipment, scheme, and related risk analysis of mechanical connecting aisle construction. In this study the work breakdown structure-risk breakdown structure combined with the expert investigation method is used to comprehensively identify the construction process, construct the risk index system of mechanical connecting aisle construction, determine the initial risk value, and comprehensively use the fuzzy-analytic hierarchical process to establish a fuzzy complementary judgment matrix, obtain the risk-weighted correction value, and quantitatively evaluate the risk source level of the mechanical connecting aisle construction. Based on the assessment method, the risk assessment of the mechanical connecting aisle construction project in Daqing section of Qingdao Metro Line 8 was performed, 113 potential risk sources were identified, and the comprehensive assessment obtained 7 major risk sources such as “improperly designed construction organization,” “instability of excavation surface,” and “easy leakage of lower river crossing” that were greater than the total risk average of 2.053. Corresponding risk response measures were proposed, which provided a reference for the risk assessment of similar projects in the construction of similar projects on mechanical connecting aisle construction in the Bohai mudstone stratum with high water pressure.